DETERMINAN STUNTING DI WILAYAH KERJA PUSKESMAS AWAAI KABUPATEN NIAS UTARA - Zebua, Beatric Permatasari; Nababan, Donal; Silitonga, Evawani M (Jurnal Kesmas Prima Indonesia, 2024)
Stunting rates among toddlers in the Health Center area remained high despite efforts such as counseling and supplementary feeding, which have not yielded significant results. This study aimed to identify the factors contributing to stunting among 2-5-year-olds at the Public Health Center through a cross-sectional design. Data were gathered using a questionnaire from 124 mothers, including 62 with stunted toddlers and 62 with normal ones. Bivariate analysis revealed correlations between stunting and several factors: knowledge (p = 0.003), exclusive breastfeeding history (p = 0.008), husband's support (p = 0.007), family income (p = 0.004), and diet (p = 0.000). The most influential factor was exclusive breastfeeding history (p=0.04 and OR=0.235). Multivariate analysis indicated that exclusive breastfeeding history (OR=0.235; 95%CI: 0.088-0.630), husband's support (OR=0.129; 95%CI: 0.043-0.390), and diet (OR=0.068; 95%CI: 0.024-0.192) were the dominant variables related to stunting. Exclusive breastfeeding was found to reduce stunting incidence by 0.23 times compared to infants who didn't receive exclusive breastfeeding. Keywords: Knowledge, Exclusive Breastfeeding History, Husband's Support, Family Income, Diet, Stunting